The Role of the Gut Microbiome in Energy Balance With a Focus on the Gut-Adipose Tissue Axis - Xiao, Han; Kang, Sona (Frontiers in Genetics, 2020)
Obesity is a complex disease attributable to many factors including genetics and environmental influences. Growing evidence suggests that gut microbiota is a major contributing factor to the pathogenesis of obesity and other metabolic disorders. This article reviews the current understanding of the role of gut microbiota in the regulation of energy balance and the development of obesity, and how the microbiota communicates with host tissues, in particular adipose tissue.